SEKEDAR MELENGKAPI ATAU MEMENUHI SYARAT DEMOKRASI? MEMBACA TINGKAT PARTISIPASI PEREMPUAN DALAM PEMILU 2019 DI KOTA BEKASI - Choirunnisa Marzoeki (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
This article discusses about the level of women's participation in the 2019 general elections in Bekasi City. The participation of women in general elections can be seen from the participation of women as voters, an election organizers, and election participants. Based on the final voter list, there are 50.24% women voters in Bekasi, which is more than men voters. However, this large number is not correlated with women representation in legislative institutions or election organizers.The affirmative action that was fought for since the 2004 election regarding the quota of 30% for women in the parliament until the 2019 election has never been reached. The number of women's votes acquired in the 2019 elections in Bekasi City was 16% or 8 elected candidates of 50 total elected candidates. The legislative candidates with the top serial number still occupy votes. On the other hand, women candidates who have first serial number are only 24%. The representation of women in the election management as regulated in the Law on Election Organizer uses the word "pay attention to" for at least 30% (thirty percent) of women representation. The word "pay attention" implies the sense that there is no obligation or necessity for the composition of women as much as 30 percent both in the General Election Commission and in the Election Supervisory Agency. So that the number of women in election organizer is still very low, starting from the national level to the lowest level.